Sur le domaine de convergence de série de Dirichle - Miškelevičius, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Мишкелявичус. Об области сходимости ряда Дирихле A. Miškelevičius. Dirichle eilutės konvergencijos sritis